(3CfSGH GdCTQGa hCNHGQges - (3CHh GdMSf CMeO Hf jMji Hf LGHQ Hf OGhO, GdHdGPQj,J (B279 (3g` s ((3eMeO bfGhi eMeO s)
(3ChdgG (B:s
(3PcQ ehGdi QShd Gddg Udi Gddg Ydjg hSde hNOeI (B: (3RjO GdMH Hf MGQKI Hf TQGMjd Hf YHO GdYRi YGeQ Hf GdeOjfI hPdc Ef Ceg ShOGA jbGd dgG GdeOjfI cGfJ MVfJge s
(3BNQgG (B:s
(3bGd YHO Gddg Hf GdMSf , dGHfg eMeO Mjf CQGO GdESJNaGA ef GdefUhQ (B: (3jG Hfi Efi eDO Edi Gddg Mbg hddeQA ChbGJ jVQ ajgG NWCg ceG JMPQ GdYGbd Ef cGf dc YOhkG GfJgi , hjdjg GdLRA GdKGdK , hChdg NQhL eMeO Hf YHO Gddg Hf MSf hebJdg s
(3HgG fXGe GdJYbjHIs
(3ef GdfSNI GdKGfjI faSgGs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B267s
Keywords: (3GdJGQjNs